Burgers, Fast Foods, and Increased Associated Risk for Atopic Dermatitis: A Cross-Sectional Study of Dietary Habits among Young Chinese Adults in Singapore/Malaysia - Lim, Jun Jie; Lim, Eliza Yi Ying; Ng, Jun Yan; Malipeddi, Praneeth; Ng, Yu Ting; Teo, Wei Yi; Wong, Ambrose Qi Yi; Matta, Sri Anusha; Sio, Yang Yie; Wong, Yi Ru *; Teh, Keng Foo *; Smyrna Moti, Rawanan Shah *; et al. (Karger Publishers, 2024)
Background: We see increasing evidence that dietary and nutrients factors play a pivotal role in allergic diseases and recent global findings suggest that dietary habits influence the pathogenesis of atopic dermatitis (AD). Frequent consumption of fast food diets is associated with AD development. Despite the rising prevalence of AD in Asia, efforts in investigating the role of dietary habits and AD in adults are still lacking.